Mount Murchison Quadrangle (Victoria Land), Antarctic geomorphological and glaciological 1:250,000 map series. - BARONI C; FREZZOTTI M; BONDESAN A; CIMBELLI M; MENEGHEL M; OROMBELLI G; TABACCO E. I; VITTUARI L.; SALVATORE, Maria Cristina; BIASINI, Alessandro (Annals of Glaciology, 2004)
Ceomorphological and glaciological features are represented on a georeferenced satellite image mosaic of the Mount Murchison quadrangle, northern Victoria Land, Antarctica (73-74° S, 162-166°30' E), at a scale of 1 : 250 000. Landforms and deposits of glacial and periglacial environments, forms related to mass wasting, wind action, weathering and geological structures are identified and mapped. The chronological sequence of landforms and deposits, morphography and lithology is also indicated. Clacier velocities (up to 180 m a-l) and ice-front fluctuations (1964-99) were determined by analysis of aeri al photography and satellite imagery. Airborne radar surveys reveal that the greatest ice thickness (about 1500 m) is located in the grounding zone of Aviator Clacier. Up to 1000 m of ice bury the subglacial relief of Deception Plateau, Hercules Névé and the Deep Freeze Range. Snow accumulation rates (average = 170 kg m-2 a-l) exhibit an overall negative correlation with altitude and distance from the coast. The relationships among relict erosional landforms and volcanic activity provide chronological constraints for the palaeogeographic evolution of this sector of the Transantarctic Mountains.